Nación e identidad en el teatro de Rogelio Sinán - Maida Watson (Les Cahiers ALHIM)
In his three plays for children, La Cucarachita Mandinga, Chiquilinga and Lobo Go Home, the Panamanian author Rogelio Sinán presents a view of the nation that exemplifies the ideas that Benedict Anderson and Homi Bhabba discuss in their well known books. Faced with the accelerated transformations and the modernization that the advent of the Panamanian Canal bring to Panama at the beginning of the XXth century, along with the concomitant foreign influence, Sinán chooses to use Panamanian folklore and tropical animals as symbols of the mythical original nation. Nevertheless, the struggle between a political reality and one of national identity is not resolved harmoniously. Like the ants in his play Chiquilinga, who represent in the original fable the virtues of work, discipline and group effort, the solution that Sinán offers calls for a profound change in the national ideology. Without exonerating the foreign powers of blame, Sinán nevertheless suggests another solution through the use of animal symbols, the function of space and elements of Panamanian folklore.